Probe into the Target and Mechanism of Jianpi Xiaoke Prescription for Treating Type 2 Diabetes Mellitus through miRNA Expression Profiling. (15th December 2020) - Guo, Qiuyue; Xu, Yunsheng; Li, Jie; Luo, Dan; Li, Jun; Xu, Cankun; Huang, Yanqin
Abstract : Object . To probe into the target and molecular mechanism of Jianpi Xiaoke (JPXK) prescription in the treatment of type 2 diabetes through high-throughput microRNA (miRNA) sequencing. Methods . Ten of the 31 SPF male Wistar rats were randomly taken as the control group; the remaining rats were fed a high-sugar and high-fat diet, combined with Streptozotocin (STZ, 35 mg/kg) that induced a type 2 diabetes model. The model rats were randomly divided into model groups ( n  = 11) and the JPXK group ( n  = 10). After 8 weeks of JPXK intervention, we detected the function of islet cells through HE staining and ELISA. High-pass sequencing technology was adopted to identify the differential expression of miRNA to explore the target of JPXK treatment, assess the relevant target genes, conduct functional analysis, and lastly verify the sequencing data by qRT-PCR. Results . After treatment, FPG, FINS, and HOMA-IR levels of the treatment group improved significantly compared with those of the control group (P < 0.05 ). Among the miRNAs differentially expressed between the model group and the control group, there were 7 reversals after JPXK treatment, including miR-1-3p, miR-135a-5p, miR-181d-5p, miR-206-3p, miR-215, miR-3473, and miR-547-3p (log2FC ≥ 1 or ≤ −1, P < 0.05 ). Besides, the 1810 target genes associated with these 7 miRNAs were assessed by multiMiR. According to the results of the GO and KEGG analyses, they were associated with biological processes (e.g., glucose transport and fat cell formation), and it covered multiple signaling pathways, capable of regulating islet cell function (e.g., MAPK, PI3K-Akt, Ras, AMPK, and HIF-1 signaling pathways). The PCR verification results were consistent with the sequencing results. Conclusion . This discovery interpreted the potential therapeutic targets and signaling pathways of JPXK prescription against T2DM based on miRNA expression profiling. In conclusion, our research provided novel research insights into traditional Chinese medicine (TCM) treatment of diabetes.